Multidimensional outcome after endovascular or microsurgical occlusion of ruptured intracranial aneurysms – Comparative analysis of a prospective Swiss multicenter study - Vincens Kälin; Martin N. Stienen; Olivia Zindel-Geisseler; Noemi Dannecker; Yannick Rothacher; Ladina Schlosser; Julia Velz; Martina Sebök; Noemi Eggenberger; Adrien May; Philippe Bijlenga; Ursula Guerra-Lopez; et al. (Brain and Spine)
Introduction: Despite advances in cerebral aneurysm treatment, information on detailed outcomes remains limited. We compared complications and multidimensional outcomes in alert aneurysmal subarachnoid hemorrhage (aSAH) patients (GCS ≥13) who received clipping or coiling after individualized decisions were made through multidisciplinary board discussions. Research question: Are there significant differences in multidimensional outcomes between clipping and coiling treatments for alert aSAH patients when treatment selection is individualized? Material and methods: Within the prospective MoCA-DCI study (ClinicalTrials.gov identifier: NCT03032471), patients with a GCS of 13–15 72h post-aSAH in six neurovascular centers underwent neuropsychological (Montreal Cognitive Assessment; MoCA), neurological (National Institutes of Health Stroke Scale; NIHSS), headache (visual analog scale; VAS), disability (modified Rankin Scale; mRS) and health-related quality of life (EuroQol Five Dimensions; EQ5D) assessments within 72h, 14 days and three months after aSAH. We compared these multidimensional outcomes and complications for clipped and coiled patients. Results: Of 126 patients (mean age 53.8 years; 63.9 % female), 84 were coiled and 42 clipped. MoCA scores for clipped vs coiled patients were 23(7) vs 23(8; p = 0.250), 25(8) vs 28(5; p = 0.346), and 27(4) vs 28(5; p = 0.481). Normal cognition (MoCA ≥26) was achieved within 72h by 28.6 % of coiled and 40.5 % of clipped patients (p = 0.179). Complication rates were similar, though surgical patients had higher intraprocedural rupture rates (p = 0.027). Clipped patients reported higher headaches at three months (p = 0.013), while NIHSS, mRS and EQ5D showed no differences. Discussion and conclusion: After interdisciplinary selection of the most appropriate treatment, similar favorable outcomes can be achieved in alert aSAH patients.